Prevalence of trachoma in a population of the upper Rio Negro basin and risk factors for active disease - Cruz, Antonio Augusto V.; Medina, Norma H.; Ibrahim, Marlon M.; Souza, Roberto M.; Gomes, Uilho A.; Gonçalves, Glauco F. O. R. (Taylor & Francis, 2008)
Purpose: To determine the prevalence of trachoma in Sao Gabriel da Cachoeira (SGC), the only urban community of the upper Rio Negro Basin of the Amazon state in Brazil, near the Colombian border, and to investigate the risk factors associated with the active forms of the disease. Methods: A total of 1702 people (440 children up to 9 years and 1069 adults aged 15 years and above) were examined. The sample was selected from a probabilistic household sampling procedure based on census data and a previous study of trachoma prevalence in Sao Gabriel da Cachoeira. A two-stage probabilistic household cluster sample was drawn. Household units were randomly selected within each cluster. A variety of socioeconomic and hygiene variables were studied in order to determine the risk factors for active trachoma in a household. Results: The total prevalence of trachoma was 8.9%. Prevalence of active trachoma (TF and/or TI) in children aged 1-9 years was 11.1% and trachomatous trichiasis in adults aged 15 years and above was 0.19%. Trachomatous scarring reached a peak of 22.4% for subjects between 50 to 60 years of age. Corneal opacity occurred in subjects aged 50 years and older with a prevalence of 2.0%. No sex effect was found on the overall prevalence of trachoma in SGC. Risk factors associated with active trachoma were mainly related to poor socioeconomic indicators. Conclusions: Despite the ubiquitous presence of water, the analysis of the risk factors associated with the active forms of the disease supports the idea that a low personal standard of hygiene and not water availability per se, is the key factor associated with trachoma. Copyright © 2008 Informa Healthcare USA, Inc.
Keywords: Brazil; Prevalence; Risk factors; Trachoma; adolescent; adult; child; cornea opacity; female; human; hygiene; infant; major clinical study; male; prevalence; priority journal; risk factor; scar formation; socioeconomics; trachoma; trichiasis; water supply; Adolescent; Adult; Child; Child, Preschool; Female; Health Surveys; Humans; Infant; Male; Middle Aged; Risk Factors